COMPARATIVE EVALUATION OF HOT PEPPER PUNGENCY BY ORGANOLETIC AND INSTRUMENTAL METHODS - H. G. Kekina; N. A. Golubkina; M. I. Mamedov; H. A. Djos; O. N. Pishnaya; S. M. Nadezhkin (Овощи России)
A comparative evaluation of 20 hot pepper varieties according to pungency determination by organoleptic, spectrophotometric methods, and HPLC has been done. The capsaicin concentrations were in the range 1.0-7.15 mg/g d.w., pungency value - (17440-153120) SHU. A direct correlation between organoleptic analysis and capsaicin content determined spectrophotometrically and using HPLC was determined. Spectrophotometric method was shown to give elevated values of capsaicin concentration especially in samples with low pungency, that was related to lack of chromatographic separation of capsaicin extract.